2006
DOI: 10.1007/s10459-005-5491-2
|View full text |Cite
|
Sign up to set email alerts
|

Being a Clinical Educator

Abstract: What is it like to be a clinical educator? How do clinical educators experience and describe their continuing journey of becoming a clinical educator? Within the model developed in this research, dimensions of being a clinical educator were identified. These dimensions include (a) having a sense of self (and the impact of bringing self into the clinical educator's role), (b) having a sense of relationship with others (and the place of this "interactive self" as a central feature of clinical education), (c) hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 22 publications
5
53
0
4
Order By: Relevance
“…a guide to the diagnosis and remediation of different types of clinical reasoning difficulties) , and teacher-centered faculty development. Altogether this amounts to no less than a cultural and organizational change (Steinert, 2011) which should help clinician-teachers act effectively, based on well-grounded educational scripts (Côté & Bordage, 2012) Arming clinician-teachers with a strong sense of "being clinical educators" (Higgs & Mcallister, 2006) should ultimately improve outcomes for learners.…”
Section: More Faculty Supportmentioning
confidence: 99%
“…a guide to the diagnosis and remediation of different types of clinical reasoning difficulties) , and teacher-centered faculty development. Altogether this amounts to no less than a cultural and organizational change (Steinert, 2011) which should help clinician-teachers act effectively, based on well-grounded educational scripts (Côté & Bordage, 2012) Arming clinician-teachers with a strong sense of "being clinical educators" (Higgs & Mcallister, 2006) should ultimately improve outcomes for learners.…”
Section: More Faculty Supportmentioning
confidence: 99%
“…La práctica totalidad de los profesores opina que los factores clave para una enseñanza práctica adecuada son la figura de un buen médico docente y la actitud e interés del alumno [7]. Además, los encuestados consideraron que la asistencia y participación del alumno en las actividades cotidianas de la práctica clínica, su integración en los diferentes servicios con la posibilidad de llevar a cabo actividades ante el paciente, y su rotación por un menor número de servicios con una mayor permanencia en ellos, es fundamental para lograr los objetivos marcados [8,9].…”
Section: Discussionunclassified
“…La valoración más alta de los lugares idóneos para la práctica clínica fue, por este orden (en escala 0-10): áreas de hospitalización (7,9), consultas (7,4), urgencias (7,2), quirófanos (7), exploraciones especiales (6,9) y centros de salud (6,9).…”
Section: Participación Del Alumnadounclassified
“…Stenfors-Hayes et al similarly found that medical and dental teachers' shared a core conception of development as a teacher involving content expertise, with some teachers adding a layer of pedagogical expertise. 34 …”
Section: Can Different Viewpoints In Terms Of Supervisors' Educationamentioning
confidence: 99%